O'Malley, Jan (London, 2011)
2011 "O'Malley, Jan", 2011, HistoryTalk Jan is the author of "The Politics of Community Action" that has become a key text in understanding the community struggles of the 1960s/ 1970s. Jan was involved in the Fidelity Radio struggle in North Kensington and the interview gives detailed information about the causes of the dispute and the dynamics of the relationship between workers, unions and local community activists. The building of the Westway also impacted on their activities with issues of open space, play space, community centres etc. This continues into the 1970s on a wider level and into the 1980s around health Fightback.